2006
DOI: 10.1007/s11095-006-9082-6
|View full text |Cite
|
Sign up to set email alerts
|

Agglomerate Strength and Dispersion of Salmeterol Xinafoate from Powder Mixtures for Inhalation

Abstract: The outcomes of this research demonstrated how agglomerate structure influenced dispersion and the key role of fine lactose particle size in SX dispersion from mixtures for inhalation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 11 publications
3
42
0
Order By: Relevance
“…Nevertheless, the FPF of salmeterol xinafoate from this binary mixture significantly decreases and is less than half of that of the formulation employing the drug only. Thus, the fine-particle generation of the drug from the carrier particles into the air stream was significantly less than that from aerosolising salmeterol xinafoate alone [83]. Inadequate drug/carrier separation is one of the main explanations for the low deposition efficiency encountered with DPIs [10].…”
Section: Carrier-particle Surface Modificationmentioning
confidence: 99%
“…Nevertheless, the FPF of salmeterol xinafoate from this binary mixture significantly decreases and is less than half of that of the formulation employing the drug only. Thus, the fine-particle generation of the drug from the carrier particles into the air stream was significantly less than that from aerosolising salmeterol xinafoate alone [83]. Inadequate drug/carrier separation is one of the main explanations for the low deposition efficiency encountered with DPIs [10].…”
Section: Carrier-particle Surface Modificationmentioning
confidence: 99%
“…The first one supposes the occupation of the high-energy sites on the carrier by the lactose fine particles leaving low-energy sites available for the API, thus enabling greater API detachment (22,34). In the second theory also called redistribution theory, aggregates of API and lactose fine particles termed multiplets are formed enabling greater API detachment (22,(34)(35)(36). At the present time, there is no preferential theory to explain the influence of lactose fine particles.…”
Section: Influence Of Carrier Particle Sizementioning
confidence: 99%
“…However, these studies were based on relatively small datasets, and the carriers used have mainly been different coarse fractions of lactose. It has also been shown that the particle size distribution of the added fine lactose is an important factor in determining whether the DPI formulation performance increases as more lactose fines are added, with finer sub-cuts of the lactose known to be more effective in improving DPI performance (11,(23)(24)(25). Following on from the hypothesis of Shur et al that increased cohesion of the carrier results to an increased DPI formulation performance (12), the study reported here aimed to investigate the influence of the addition of extrinsic lactose fines with different process histories (micronized vs. milled), and thus size distributions, to the bulk flow and fluidization properties of a wide range of different carriers, and aimed to investigate whether the increased cohesion would universally account for the improved DPI performance for a wide selection of lactose carriers.…”
Section: Introductionmentioning
confidence: 99%